Electrobioremediation of an unsaturated soil contaminated with hydrocarbon after landfarming treatment - Acuña,A.J. (2010)
The electro-bioremediation is a technique that is used for the remediation of hydrocarbon contaminated soils. The aim of this study is to explore the electro-bioremediation of an unsaturated soil, contaminated with hydrocarbon waste generated by the oil industry activity in the area and previously remediated by landfarming, to in order to increase the removal of polyaromatic hydrocarbons. The sample was put in a three-compartment electro-bioremediation glass cell of 58 cm long, the lateral compartments containing the electrolyte; we used bridges of ammonium phosphate to connect the electrolyte with the soil sample in the central compartment. A potential difference of 0.5 V cm-1 was applied to the electro-bioremediation cells for 60 days. A second cell was used for control and no current was applied to it. The monitoring was carried out by a counting cell and measuring of n-alkanes and polyaromatic hydrocarbons using GC mass. The results showed that this technology has good potential to increase the biodegradation of n-alkane hydrocarbons and polyaromatic hydrocarbons such as phenanthrene, 1-3-metilphenanthrene, chrysene, 3-methylchrysene, 6-methylchrysene, benzo(b)fluoranthrene and benzo(ghi)pyrene which, without the application of direct current, were not biodegraded by microorganisms in the soil. The use of salt bridges maintained the pH between values that are compatible with the degrading bacterial community.